Omi/HtrA2 Protease Associated Cell Apoptosis Participates in Blood-Brain Barrier Dysfunction - Hu, Yueyu; Bi, Yong; Yao, Danhua; Wang, Pengfei; Li, Yousheng (Frontiers in Molecular Neuroscience, 2019)
Background: We sought to determine whether interference of Omi/HtrA2 by RNA interference or UCF-101 treatment improves sepsis-induced loss of BBB structural and functional integrity in vitro using human cerebral microvascular endothelial cell line (hCMEC/D3) and if so, to identify potential mechanisms by which Omi/HtrA2 protease participates in blood-brain barrier dysfunction in sepsis. Methods: hCMEC/D3 cell monolayers were exposed to different concentrations of LPS (0 to 50μg/mL) over experimental period. Pharmacological or gene manipulation (by silencing RNA of Omi/HtrA2) approaches were used to investigate specific molecular mechanisms implicated in sepsis-induced Omi/HtrA2 translocation, cell apoptosis and BBB dysfunction. Results: LPS affects hCMEC/D3 TJ permeability in a dose- and time-dependent manner. LPS intervention resulted in a significant loss of BBB integrity, as demonstrated by reduced TEER (by 26 %) and a parallel increase in paracellular permeability to FITC- (4kDa) dextrans across hCMEC/D3 monolayers. The abrogation of Omi/HtrA2 by UCF-101 or Omi/HtrA2 shRNA reduced LPS-induced brain endothelial cell apoptosis, resulted in a significant improvement on LPS-induced loss of BBB integrity as well as decreased LPS-induced loss of occludin, claudin-5 and ZO-1 expression in hCMEC/D3 cells. Omi/HtrA2 regulates LPS-induced endothelial cell apoptosis by translocating from mitochondria into cytosol and inducing X-linked inhibitor of apoptosis protein (XIAP) degradation. UCF-101 administration or Omi/HtrA2 shRNA intervention did attenuate the degradation of XIAP, PARP cleavage, and caspase-3 cleavage. However, only UCF-101 partly prevented the mobilization of Omi/HtrA2 from the mitochondria to the cytosol after LPS intervention. That abrogation of Omi/HtrA2 by UCF-101 or Omi/HtrA2 shRNA resulted in a significant improvement on LPS-induced decrease of mitochondrial membrane potential. Oxidative stress was significantly increased in the LPS treated group compared to the control or NC-shRNA group. However, abrogation of Omi/HtrA2 by UCF-101 or Omi/HtrA2 shRNA didn’t significantly improve oxidative injury. Conclusions: Our data indicated a potential role for Omi/HtrA2 in regulating LPS-induced cell apoptosis and BBB integrity by translocating from mitochondria into cytosol in brain endothelial cells. Omi/HtrA2 increases apoptosis through a mitochondrial pathway dependent, caspase-mediated mechanism, which involves degradation of a critical antiapoptotic molecule, XIAP and influence on mitochondrial membrane potential.